Letter
029-0140-001 Registered Office: 1 Balloon St. Manchester, 4. TELEGRAPHIC ADDRESS: "WHOLESALE ALD" LONDON. TELEPHONE: ROYAL 7221. Co-operative Wholesale Society Limited, BANKERS Our Reference WM/AP. Your Reference 99, LEMAN STREET, LONDON. E.1 7th June, 1937. Sir Walter Citrine, Transport House, Westminster, S.W.1. Dear Sir, We confirm having informed you through our Westminster Office that we had today received a telegram as under, "Please wire immediately ten thousand pounds to the order of Georges Moha twenty one rue Jean Baptiste Dumas Paris through National City Bank of New York France. Schevenels Stolz." As we cannot be sure that the names purporting to sign the telegram are those of the authorised signatories we shall be glad to have your confirmation that the matter is in order. In accordance with your request we are not proceeding with the matter until we hear further from you. Yours faithfully, [signed] Manager. 292/946/29/140